CASE STUDY ON THE ROLE OF HIGH SCHOOL TEACHERS IN PROMOTING GLOBAL CITIZENSHIP SKILLS FOR DEVELOPING GLOBAL GOVERNANCE - Buxukbayev Kaiyrbek Sabitovich; Ybyrayeva Korkem Nurlanovna; Singh, Chandan Pal (International Journal of Multidisciplinary Research and Studies, 2023)
Global citizenship education (GCE) has gained significant attention to foster a more just and sustainable world. This research paper presents a case study of the Role of the Science and language teacher in implementation of GCE in a NIS, Chemistry and Biology, Shymkent, Kazakhstan. This study also focusses for the impact on understanding the GCE components after two days workshop conducted by authors. The study employs a critical analysis approach, drawing on interviews with educators as well as document analysis of “Global Citizenship understanding Scale” (GCUS) and The Respect of Differences Scale (RDS) pre and post workshop. Researchers tried to find the teacher’s skill to integrate GCE curricula and related policies. The findings reveal both promising practices and challenges in GCE implementation, including the need for more teacher training, increased funding, and better coordination among stakeholders. The paper also discusses the impact of GCE on students' knowledge, skills, attitudes, and behaviors, highlighting the potential for GCE to promote global-mindedness and social justice. However, it also identifies limitations and suggestions about the practices in GCE inside NIS, Chemistry and Biology, Shymkent, Kazakhstan. The paper concludes with implications for future research and policy development in GCE in NIS CIS, Shymkent. Researchers emphasized the importance of a more comprehensive and equitable approach to global education.